Positive drug tests from supplements - Burke, L. M. (Sportscience, 2000)
About the risk to be tested positive following supplement intake and how to avoid this. There is a small but real risk that athletes will test positive to a banned substance as a result of ingesting supplements and sports foods. Lack of regulation of quality control and labeling of products in the supplement industry makes it impossible to identify supplements and sports foods that are risk free. Incentives or punishments for the supplement industry to improve manufacturing processes are therefore needed. Meanwhile sports authorities place the responsibility for a positive test with the athlete, necessitating better education of athletes, coaches and support staff.